The dosimetric comparison of Truebeam and Cyberknife treatment planning systems dose calculation accuracy for brain SRS treatment on Randophantom. (September 2016) - Mabhouti, H.; Sanli, E.; Cebe, M.S.; Codel, G.; Pacaci, P.; Serin, E.; Doyuran, M.; Kucukmorkoc, E.; Altinok, A.; Canoglu, D.; Kucuk, N.; Acar, H.; et al.
Abstract : Purpose: Brain stereotactic radiosurgery (SRS) involves the use of precisely directed, single session radiation to create a desired radiobiologic response within the brain target with acceptable minimal effects on surrounding structures or tissues. In this study, the dosimetric comparison of target and OAR doses in Truebeam 6 FFF and Cyberknife M6 machines were made. Methods: Treatment planning were done using 2 full arc VMAT technique with 6 FFF beam on the CT scan of Randophantom simulating the treatment of sterotactic treatments for one brain metastasis. The dose distribution were calculated using Eclipse treatment planning system (TPS) with Acuros 13 algorithm. In addition treatment planning for same target volume were also done for Cyberknife M6 machine using Multiplan TPS with Monte Carlo algorithm. Target and brainstem, chiasm, optic nerve, lense median doses were measured using OSL dosimeters. The measured and calculated doses were compared. Results: The calibration of OSL dosimetry were done at first. Target dose measurements made using the OSL dosimetry for both Cyberknife and Truebeam within the measurement uncertainty of 3.1%. The max differences between OSL measured and Eclipse calculated OARs doses were 3.3%, 4.5%, 5.6% and 6.2% for brainstem, chiasm, optic nerve, lense doses respectively. For cyberknife treatment, the max differences between OSL measured and Monte Carlo calculated OARs doses were 0.9%, 1.2%, 1.6% and 2.2% for brainstem, chiasm, optic nerve, lense doses respectively. Conclusion: The study shows that dosimetrically comparable plans are achievable Cyberknife and Linac. However, a better conformity, target coverage, less OAR dose and insteeper dose fall off away from the target is achieved with Cyberknife. Monte carlo calculation algorithm predicts the OARs doses more accurately than Acuros algorithm.